2022
DOI: 10.1039/d2cp02625b
|View full text |Cite
|
Sign up to set email alerts
|

Designing the structure and relevant properties of semiclathrate hydrates by partly asymmetric alkylammonium salts

Abstract: Semiclathrate hydrates are host-guest materials that form from ionic guests and water. There are numerous options for the ionic guests, such as quaternary ammonium salts, to obtain functional properties of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The relationship between molecular structures of quaternary ammonium cations and the combined cages which can be stabilized by the cations is shown in Fig. 4, e.g., well symmetric ions such as TBA (or N4444) ( 35 ) and tetra- i -pentylammonium (Ni5i5i5i5) ( 16 ) and partly asymmetric tri- n -butyl, n -pentylammonium (N4445) ( 41 ) cations, where, in abbreviation, N, 4, 5, and i5 denote nitrogen, n -butyl, n -pentyl, and i -pentyl, respectively. The n -hexyl chain is the only guest moiety that can stabilize the true form of the P cage with the 6true¯ m 2 symmetry required for the HS-I structure, which has never been stabilized by the other guests.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between molecular structures of quaternary ammonium cations and the combined cages which can be stabilized by the cations is shown in Fig. 4, e.g., well symmetric ions such as TBA (or N4444) ( 35 ) and tetra- i -pentylammonium (Ni5i5i5i5) ( 16 ) and partly asymmetric tri- n -butyl, n -pentylammonium (N4445) ( 41 ) cations, where, in abbreviation, N, 4, 5, and i5 denote nitrogen, n -butyl, n -pentyl, and i -pentyl, respectively. The n -hexyl chain is the only guest moiety that can stabilize the true form of the P cage with the 6true¯ m 2 symmetry required for the HS-I structure, which has never been stabilized by the other guests.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis and characterization of the N3444 and N4445 cations were carried out by the same process in our previous study. 61 The resulting bromide salts were converted to chloride salts by ion exchange resin (IRA402BL CL Organo Co. Ltd, Tokyo, Japan), and the obtained solution was neutralized by hydrogen chloride solution (0.2 mol L −1 , FUJIFILM Wako Pure Chemical, Co.). It was confirmed that byproducts of tri- n -butylamine and bromide ion remaining in the converted salts were less than 0.1 mass percent using 1 H NMR and an ion chromatograph device (ICS-2000, Dionex Co.).…”
Section: Methodsmentioning
confidence: 99%
“…Further description of the melting temperature measurement method can be found elsewhere. [53][54][55][56]61…”
Section: Melting Temperature Measurementsmentioning
confidence: 99%
See 2 more Smart Citations